Organizational Culture at PT Kereta Api Indonesia (Persero) Based on the Level of Basic Assumptions, Values, and Artifacts - Destyananda, Nanditya Putri; Suaedi, Falih (Universitas Muhammadiyah Bengkulu, 2022)
This study aims to determine the organizational culture applied at PT Kereta Api Indonesia (Persero) based on the level of organizational culture, namely: basic assumptions, values, and artifacts. Organizational culture plays a major function in modeling the behavior and performance of the company through the collective efforts of each member. The research method used is qualitative with emphasis on documentation as a data collection technique in this study. Meanwhile, data analysis was carried out in a narrative manner. The empirical findings in this study focus on organizational culture at PT Kereta Api Indonesia (Persero) which as a whole shows the company's success in improving management and employee performance. In addition, it has a significant impact on customer satisfaction and the good image of the company. PT Kereta Api Indonesia (Persero) provides excellent service to customers, where they are a top priority for the company. The change in orientation to excellent service to customers makes PT Kereta Api Indonesia (Persero) able to compete in the global market era.Keywords: organizational culture; PT Kereta Api Indonesia (Persero); organizational culture level